Mechanical design and simulation of wwo-Wheeled wheelchair using solidworks - Altalmas, Tareq, M.; Ahmad, Salmiah; Akmeliawati, Rini; Sidek, Shahrul Na'im; Aula, Abqori (2013)
This article is presented a new design of two-wheeled wheelchair that can balance on two wheels to make it suitable in the narrow areas, especially in the domestic environments; it has the ability to extend the height of the chair to help the user to act independently in the life for example, in the library to pick and put books on the shelves. The 3D model has been built up using SolidWorks Software. Nowadays, SolidWorks environment is considered as a powerful tool that is helping designer to design products and attain its performance before physical prototype stage. SolidWorks simulation model has been employed to test the frame of the wheelchair under the weight of the human body and the upper part of the wheelchair. The static analysis has been done on the frame using steel and aluminium; however the aluminium material has been selected due to its light weight